ENCOURAGE PEOPLE’S INTEREST TO DO CASH WAQF - Puji Hadiyati; Annisa Indah Gladys; Muhammad Iqbal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2020)
This study aims to identify the community interest to cash waqf. The population of this study are people living in Jabodetabek area. Variables used in this study include knowledge, understanding, awareness and promotion of community interest to cash waqf. Simple Random Sampling is the sampling method in this research and regression with ordinary least squared approach become its analysis method. The results show that knowledge and understanding do not have an influence on the community interest to doo cash waqf, while the awareness and promotion variables affect the community interest to do cash waqf.